Analisis Faktor Yang Berhubungan Dengan Kesiapan Perawat Dalam Menangani Cardiac Arrest Di Ruangan Iccu Dan Icu Rsu Anutapura Palu - Aminuddin, (Jurnal Keperawatan Soedirman, 2013)
The number of deaths in public hospitals Anutapura Palu who suffer from heart disease . In 2010 some 20 cases , in 2011 some 31 cases , in 2012 a total of 39 cases . The purpose of this study was to determine the relationship between knowledge, facilities and training of nurses in dealing with readiness Cardiac Arrest. This research is a cross sectional analytic study with a total sampling sampling using a questionnaire and checklist. Test using chi-square statistics. The results showed that there was a significant relationship between knowledge of the readiness of nurses in dealing with cardiac arrest (p:0.001 ) , there was no significant relationship between the readiness of nursing facilities in dealing carsdic arrest (p:0.301 ) , no significant relationship with the readiness of nurses training in handling cardiac arrest (p:0.025) . Knowledge and training related to the readiness of nurses in addressing cardiac arrest. Facility does not displays the value of nurses in readiness menagani cardiac arrest. It is expected that other researchers can develop this research with other variabel.